FAKTOR-FAKTOR DETERMINAN REPUTASI PERUSAHAAN PADA RESTORAN CEPAT SAJI DI JAKARTA - Sefvinur Yuliana Putri; Hermi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
This study aims to analyze about determinant factors the company's reputation such as social responsibility, customer satisfaction, customer loyalty and brand image on the company's reputation. This study uses primary data obtained by distributing to respondents with google form. The population in this study are consumers of fast food restaurants in DKI Jakarta. The sample used is consumers from fast food restaurants through a questionnaire used as many as 260 respondents. The sampling technique was determined by using a non-probability sampling method with purposive sampling type, namely the way of taking samples not randomly but using certain criteria, among other consumers who bought fast food restaurant products, especially in DKI Jakarta at least 2 times and at least 17 years old and knew about corporate social responsibility conducted through a questionnaire used. The data testing technique used in this study used multiple regression analysis which was operated through the SPSS version 25 program. The results of this study indicate that partially and simultaneously corporate social responsibility, customer satisfaction, customer loyalty and brand image have a positive and significant effect on company reputation.